Aesthetic perception, acceptance and satisfaction in the treatment of carious lesions with silver diamine fluoride: Scoping review - Sri Pandu Utami; Putri Azura Jumer; Laveniaseda Laveniaseda (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2022)
Background: With a frequency of 69%-79%, dental caries is one of the most prevalent diseases in the world. Untreated cavities are linked to pain, discomfort with eating, drinking, sleeping, and smiling, which has an impact on a child's overall health and development. To stop active carious lesions, one such technique involves applying SDF as a cheap, antibacterial, and remineralizing agent. Objective: How is the aesthetic perception, acceptance, and/or satisfaction of patients, parents, and professionals towards the treatment of carious lesions with SDF. Methods: The method used in this study uses the literature study method. The data was carried out by searching the PubMed, ScienceDirect, Google Scholar and Google databases. Results: Parents concur that SDF is a significant breakthrough in the management of ECC that has the potential to alter the conventional approach to treating caries. They appreciate the non-invasive, painless, and efficient therapy for carious lesions because it delays further degradation and, in the end, spares them from having to undergo surgery under general anesthesia. Conclusion: Due to its simplicity of usage, the use of SDF has recently attracted attention. It is a promising tactic that can be extensively applied in a variety of populations, including those who refuse restorative treatment.